New species, redescription and taxonomic notes in the Dichotomius (Luederwaldtinia) batesi (Harold) species-group (Coleoptera: Scarabaeidae: Scarabaeinae) - Vaz-De-Mello, Fernando Z.; Nunes, Rafael V. (Zootaxa, 2016)
This paper deals with taxonomic issues of the Dichotomius (Luederwaldtinia) batesi (Harold) species-group. We describe Dichotomius benesi n. sp. from Panama, and redescribe and designate a lectotype for Dichotomius ocellatopunctatus (Felsche) from Venezuela, both hemi-brachypterous species. We also do brief comments on the taxonomy of this species-group. Dichotomius joelus, previously assigned to this group, is here considered to be a new synonym of D. opacipennis and then to belong to Dichotomius geminatus species-group.